2022
DOI: 10.1039/d2ra05674g
|View full text |Cite
|
Sign up to set email alerts
|

A crystal defect led zero thermal quenching β-NaYF4 : Eu3+,Dy3+ red emitting phosphor

Abstract: VY vacancies make a predominant contribution to the zero thermal quenching property of β-NaYF4 : 0.065Eu3+,0.003Dy3+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…The Eu 3+ and Yb 3+ are incorporated into the matrix. In our previous studies, we found that the down-conversion luminescent ions: Sm 3+ , Dy 3+ , and Tb 3+ lead to a decrease of thermal luminescent stability of Eu 3+ , despite the existence of an energy transfer effect. Therefore, we tried to utilize upconversion ion Yb 3+ to improve the ZTQ property of Eu 3+ in this study.…”
Section: Introductionmentioning
confidence: 85%
“…The Eu 3+ and Yb 3+ are incorporated into the matrix. In our previous studies, we found that the down-conversion luminescent ions: Sm 3+ , Dy 3+ , and Tb 3+ lead to a decrease of thermal luminescent stability of Eu 3+ , despite the existence of an energy transfer effect. Therefore, we tried to utilize upconversion ion Yb 3+ to improve the ZTQ property of Eu 3+ in this study.…”
Section: Introductionmentioning
confidence: 85%